Masaken
Unknown Member
![1654071936039.png](/data/attachments/35/35702-70de0bf2ec6fbfdd7fad16a181406c6e.jpg)
hello, i've found the answer to part a, which i've found is x + y(b-4)^2 = 2b-4. but with part b (for both i and ii), i've subbed in b = 0 and b = 6 into the equations and i've gotten answers completely different to the correct ones (i got x + 16y + 4 = 0 and x + 4y - 8 = 0 respectively). the answers in the textbook say part a is correct, and the worked solutions also say i have to sub in b = 0 and b = 6 yet they're getting different answers to mine. where did i go wrong?